2021
DOI: 10.3390/su132313032
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Residents’ Perceptions and Attitudes towards Sustainable Tourism Development in Traditional Villages: The Lens of Stakeholder Theory

Abstract: As Chinese traditional villages are receiving increasing attention from the country, society and business in terms of sustainable tourism development, their residents’ perceptions have not been thoroughly investigated. To contribute to the literature, this qualitative study, which was based on stakeholder theory, conducted semi-structured in-depth interviews with 12 different stakeholders in Hongcun, one of the most well-known traditional villages in China. Using grounded theory approach, this study found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 47 publications
2
21
0
Order By: Relevance
“…However, this does not seem to be the perception of residents, entrepreneurs, public authorities and even the entity that represents a large part of the projects in Vale dos Vinhedos, since most of them report the changes in the landscape as a positive or neutral factor, without negative interference in the development of the territory. These results corroborate the findings of Song, Zhu and Fong (2021) who observed that residents value the fact that tourism helps to preserve local natural resources, suggesting improvements in public space such as acquisition of equipment, street appearance and availability of green spaces. On the other hand, Eusébio et al (2023) observed that, even though wine tourism is based on natural resources, the environmental dimension seems to be less relevant for residents.…”
supporting
confidence: 89%
“…However, this does not seem to be the perception of residents, entrepreneurs, public authorities and even the entity that represents a large part of the projects in Vale dos Vinhedos, since most of them report the changes in the landscape as a positive or neutral factor, without negative interference in the development of the territory. These results corroborate the findings of Song, Zhu and Fong (2021) who observed that residents value the fact that tourism helps to preserve local natural resources, suggesting improvements in public space such as acquisition of equipment, street appearance and availability of green spaces. On the other hand, Eusébio et al (2023) observed that, even though wine tourism is based on natural resources, the environmental dimension seems to be less relevant for residents.…”
supporting
confidence: 89%
“…Regarding the environmental dimension, residents value the fact that tourism helps preserve local natural resources and may lead to improvements in the public space, such as through public facilities, street appearance and the availability of green spaces. However, tourism can also be perceived as an activity that can contribute to environmental degradation and pollution (Song et al , 2021).…”
Section: Conceptual Frameworkmentioning
confidence: 99%
“…A review of the literature reveals that numerous studies have been undertaken into the attitudes and perceptions of local people on issues related to tourism development (Song et al, 2021;Govender et al, 2021;Nchor et al, 2021;Nguyen, 2020). The key factors that in uence local people's perceptions and attitudes toward tourism development include economic (Linderová et al, 2021) sociocultural factors (Meimand et al, 2017), and environmental impacts (Ravikumar et al, 2022).…”
Section: Local Communities: Perception and Participationmentioning
confidence: 99%